2012
DOI: 10.1002/pa.1437
|View full text |Cite
|
Sign up to set email alerts
|

Low‐profit Limited Liability Companies (L3Cs)

Abstract: This paper introduces the Low‐profit Limited Liability Company (L3C) form to the public affairs literature. The L3C is a new legal form of business entity emerging in the USA. As a form of social enterprise, L3C firms use a marketplace approach to solve social problems. The L3C form represents a radical transformation of capitalist enterprise, in that a social mission trumps profit generation. The emergence of the social enterprise movement has the potential to shift stakeholder expectations about appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…In some cases, these organizations develop independently from a specific institutional framework, while in other cases, new regulations have been introduced to foster the development of these new organizations and to safeguard stakeholders from possible greenwashing practices (Stecker, 2016). Indeed, in many countries, there are efforts to develop legal frameworks that are capable of embracing the complexity of new organizational entities that are oriented toward blended ends such as BCs (André, 2015;Hiller, 2013;Robson, 2015) or low-profit limited-liability companies (L3Cs) (Artz, Gramlich, & Porter, 2012;Lang & Minnigh, 2010;Tyler, 2010), the latter with lower success (Callison & Vestal, 2010). As empirically observed by Cooney, Koushyar, Lee, and Murray (2014), several years after the promulgation of legislation for new organizational entities in many states of the US, an increasing number of companies is choosing to operate under these two new legal forms, with very rapid growth in the number of BCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, these organizations develop independently from a specific institutional framework, while in other cases, new regulations have been introduced to foster the development of these new organizations and to safeguard stakeholders from possible greenwashing practices (Stecker, 2016). Indeed, in many countries, there are efforts to develop legal frameworks that are capable of embracing the complexity of new organizational entities that are oriented toward blended ends such as BCs (André, 2015;Hiller, 2013;Robson, 2015) or low-profit limited-liability companies (L3Cs) (Artz, Gramlich, & Porter, 2012;Lang & Minnigh, 2010;Tyler, 2010), the latter with lower success (Callison & Vestal, 2010). As empirically observed by Cooney, Koushyar, Lee, and Murray (2014), several years after the promulgation of legislation for new organizational entities in many states of the US, an increasing number of companies is choosing to operate under these two new legal forms, with very rapid growth in the number of BCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CICs are subject to a dividend and interest cap as well as an asset lock, meaning that assets may not be transferred or distributed to any organization apart from a CIC, a charity, or a similar body established outside the UK (Nicholls 2010). In the United States, L3Cs have three main requirements: (1) they must be organized to accomplish a charitable purpose, (2) they must be primarily created neither to accumulate property nor to earn a profit, and (3) they must not be created to further any political or legislative objective (Artz, Gramlich, and Porter 2012). With both new legal forms, equity investment allows enterprises to compete on the bundle of financial return and social impact available to private investors (Henderson and Malani 2009).…”
Section: Preferential Equitymentioning
confidence: 99%
“…How does the SE model connect marketing and financing in addressing the social problems? It has been suggested that they need to garner additional sources of revenue from sustainable sources in addition to grants and donations that NPOs rely on (Artz et al, 2012). With the SE paradigm, inspired individuals thus try to confront chronic global challenges and create value at the societal level with the support of patient capital[1], thereby overcoming the lacunae of previous economic models.…”
Section: Agenda Of Social Enterprisesmentioning
confidence: 99%